Self Actualization of Libby Strout in Jennifer Niven's Holding Up the Universe Novel - Auliya, Salsabila Gina; Kuncara, Singgih Daru; Rahayu, Famala Eka Sanhadi (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
ABSTRACT This study aims to describe the process of achieving self-actualization of the main character Libby Strout in the novel of Holding Up the Universe by Jennifer Niven. The method used in this research is descriptive qualitative with a literary psychology approach namely hierarchy of needs by Abraham Maslow. The data in this study were taken from the novel, such as dialogues, narratives, and monologues. The researchers used several steps of collecting the data, such as reading novel, identifying the data, classifying the data, and reducing the data. The process of Libby achieving self-actualization is carried out by meeting other needs, such as physiology, safety and security, love and belonging, self-esteem needs. The next was, Libby Strout satisfied the self-actualization need. She satisfied some of the self-actualization’s characteristics: acceptance (self and others), the quality of detachment: need for privacy, interpersonal relationship, naturalness in behaving, autonomous functioning, independence, freshness of appreciation, resistance to enculturation, and peak experience.Keywords : Hierarchy of needs, Self-actualization, Libby StroutABSTRAK Penelitian ini bertujuan untuk mendeskripsikan proses pencapaian aktualisasi diri tokoh utama Libby Strout dalam novel Holding Up the Universe karya Jennifer Niven. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan psikologi sastra yaitu hirarki kebutuhan Abraham Maslow. Data dalam penelitian ini diambil dari novel, seperti dialog, narasi, dan monolog. Peneliti menggunakan beberapa langkah untuk mengumpulkan data, seperti membaca novel, mengidentifikasi data, mengklasifikasikan data, dan mereduksi data. Proses Libby mencapai aktualisasi diri dilakukan dengan memenuhi kebutuhan-kebutuhan lain, seperti kebutuhan fisiologi, keamanan dan keselamatan, cinta dan rasa memiliki harga diri. Selanjutnya, Libby Strout memenuhi kebutuhan aktualisasi diri. Ia memenuhi beberapa karakteristik aktualisasi diri: penerimaan (diri sendiri dan orang lain), kualitas dari detasemen: kebutuhan akan privasi, hubungan interpersonal, kealamian dalam berperilaku, fungsi otonom, kemandirian, apresiasi yang segar, resistensi terhadap enkulturasi, dan pengalaman puncak. Kata Kunci : Hirarki kebutuhan, Aktualisasi diri, Libby Strout